Good nursing practices related to the use of enteral probe (Research, Society and Development, 2021)
Objective: To identify good nursing practices related to the use of enteral probes. Methodology: Integrative review, from publications indexed in the databases: Latin American and Caribbean Literature (LILACS), Nursing Database (BDENF), Cumulative Index to Nursing and Allied Health Literature (CINAHL), pubmed portal and digital library Scientific Electronic Library Online (SCIELO). The search included studies available in full text, published between January 2014 and April 2019, in the Portuguese, English and Spanish languages related to patients over 18 years of age. Excluded those with duplicity and who did not correspond to the theme. In the consultation of the databases, the Descriptors in Health Sciences (DeCS) were used: "Feeding by tube", "Nursing care"; "Gastrointestinal intubation", associated through the bolean connector "and". Subsequently, the articles were categorized according to title, authors, journal, year of publication, country and type of study. Results: We selected 15 articles that met all established criteria, resulting in four thematic categories: "Use of protocols related to the use of enteral probe"; "Verification of enteral probe positioning"; "Knowledge about enteral nutritional therapy" and "Prevention of adverse events". Conclusion:  It was observed that good practices related to the use of enteral probego beyond the correct installation of its own, also covering the guidelines to the family and teams and mainly compliance with institutional protocols.